Technical limitations of large-scale grid-connected photovoltaic power plants in peninsular Malaysia - Lurwan, Sabo Mahmoud (2017)
Deployment of large-scale grid-connected PVs power plants requires very reliable technical evaluation to reduce electricity demand and achieve efficient utilization of electricity generated from PV. At lower PV penetration levels, it is likely that the energy mix could be under-supply utility demand, thus requiring extra units of generators, while at higher penetration levels it may oversupply demands, thus wasting generator capacity. Therefore, determining the optimum installed capacity, technical limits, and economic benefits of large-scale PV systems are the main issue for both power utilities and decision makers. Although previous studies have attempted to evaluate large-scale PV integration into the existing grid systems, the most critical limitation in these studies, which are mainly based on physical models and technical parameters (voltage and current) through simulations, is the lack of connection to spatial planning activities. Concisely, energy prediction tools and models are mostly detached from the real world (from a geographic perspective) as they generally account only for topological relations within the system, neglecting the actual topography and spatial relationships. In addition, none of these studies have incorporated the topographical, topological features and geographic information systems (GIS) to assess the technical limits of large-scale PV implementation. Thus, integrating the geographic nature of renewable energy resources (PV), accounting not only for energy-related variables but also for spatial variables, is a perennial challenge. This study describes the development and validation of an alternative method (named as the generation-demand matching model GDMM) for evaluating the large-scale implementation of grid-connected PV power plants in Peninsular Malaysia relative to its interface with the traditional power grid system. The method which composed of the optimal site, electricity generation, and electricity demand explicitly provides a detailed assessment of the temporal and spatial factors that facilitate the match between PV generated electricity and electricity demand. These evaluation factors are analyzed using simulations of PV electricity generation located at optimal sites performed using a proposed optimal site based PV performance model (PVOBM). Optimal sites along with physical constraints were mapped using a proposed optimal site definition model (ODM) combined with geographic information systems (GIS) for visualization and representation by location. PV electricity generation at different levels of penetration was predicted hourly for a year using time series analysis. This allowed comparison of electricity generation with electricity demand to evaluate the impacts of increasing levels of PV penetration, economy and emission reduction. A novel feature of the proposed method is its combination of topographical and topological map data with metric data. The ability of the new method to accurately predict the performance of PV compared to PVWatts demonstrates the robustness of the method in evaluating the technical limits of PV systems in conventional power systems.